2020
DOI: 10.1111/vop.12768
|View full text |Cite
|
Sign up to set email alerts
|

Use of free oral mucosal graft for treatment of feline eyelid agenesis in seven patients

Abstract: ObjectiveTo describe a simple and effective surgery for feline eyelid agenesis.ProcedureFree oral mucosal grafts were harvested from the upper lips of the surgical patients. A recipient bed was created by incising the conjunctiva at the conjunctival‐skin border and opening a space in the tissue with blunt dissection without removal of tissue. The free oral mucosal graft was sutured into the space with simple continuous suture pattern of 7‐0 Vicryl.ResultsEyelids were cosmetically acceptable at final examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…In the opinion of the authors, the use of HA subdermal tissue expansion described in the current report is advantageous as more tissue can be generated between the haired skin and the cornea pre‐operatively, due to mechanical creep, to make post‐operative trichiasis less likely. This is supported by our results as only 1/39 (2.5%) eyelids had trichiasis requiring a general anesthetic to resolve in the form of a Hotz‐Celsus eyelid repair (Figure 7A–H); this is considerably less than the post‐operative trichiasis rates previously reported by Warren et al 15 It is possible that in this single case in our study, the surgical excision to delineate the mucosal surface from the cutaneous surface was located in too close of a proximity to the cutaneous surface, as some germinal hair follicles emerged proximal to the grafted site.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the opinion of the authors, the use of HA subdermal tissue expansion described in the current report is advantageous as more tissue can be generated between the haired skin and the cornea pre‐operatively, due to mechanical creep, to make post‐operative trichiasis less likely. This is supported by our results as only 1/39 (2.5%) eyelids had trichiasis requiring a general anesthetic to resolve in the form of a Hotz‐Celsus eyelid repair (Figure 7A–H); this is considerably less than the post‐operative trichiasis rates previously reported by Warren et al 15 It is possible that in this single case in our study, the surgical excision to delineate the mucosal surface from the cutaneous surface was located in too close of a proximity to the cutaneous surface, as some germinal hair follicles emerged proximal to the grafted site.…”
Section: Discussionsupporting
confidence: 90%
“…Our technique differs due to the utilization of HA subdermal tissue expansion in conjunction with this technique. Warren et al reported 2/14 (14.2%) treated eyelids required post‐operative cryoepilation due to ongoing trichiasis 15 . In the opinion of the authors, the use of HA subdermal tissue expansion described in the current report is advantageous as more tissue can be generated between the haired skin and the cornea pre‐operatively, due to mechanical creep, to make post‐operative trichiasis less likely.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations